PCSK9 inhibitors: an overview on a new promising lipid-lowering therapy. Issue 4 (April 2016) - Denegri, Andrea; Petrova-Slater, Iveta; Pasotti, Elena; Rossi, Maria Grazia; Pedrazzini, Giovanni Battista; Moccetti, Tiziano; Moccetti, Marco
Abstract : Atherosclerosis is characterized by cholesterol deposition in the arterial intima, with subsequent plaque formation and arterial disease. Low-density lipoprotein cholesterol (LDL-C) plays the most important role in the atherogenesis process, which is the substrate of cardiovascular disease and is the leading cause of death worldwide. Several studies show that a strict control of risk factors, particularly the reduction of LDL-C levels, is a cornerstone in primary and secondary prevention of coronary heart disease. Statins are currently the most effective drugs for lowering LDL-C, but the discovery of proprotein convertase subtilisin kexin 9 (PCSK9) has opened up new therapeutic options in lipid management. PCSK9 reduces LDL-receptors' recycling resulting in a decrease of LDL-C receptors on the surface of hepatocytes and an increase of LDL-C levels in plasma. Obviously, inhibition of PCSK9 has been associated with an increase of LDL-C receptors with subsequent lowering of plasma levels of LDL-C. The clinical development of monoclonal antibodies against PCSK9 has been achieved through phase I and II studies, and nowadays there are many ongoing phase III trials with promising preliminary results. The aim of this review is to update the evidence for PCSK9 monoclonal antibodies, such as evolocumab, alirocumab and bococizumab, in LDL-C management and to discuss their therapeutic perspectives based on the most recent clinical studies, with attention to side-effects.